2021
DOI: 10.1111/mpp.13155
|View full text |Cite
|
Sign up to set email alerts
|

A novel effector, CsSp1, from Bipolaris sorokiniana, is essential for colonization in wheat and is also involved in triggering host immunity

Abstract: The hemibiotrophic pathogen Bipolaris sorokiniana causes root rot, leaf blotching, and black embryos in wheat and barley worldwide, resulting in significant yield and quality reductions. However, the mechanism underlying the host-pathogen interactions between B. sorokiniana and wheat or barley remains unknown. The B. sorokiniana genome encodes a large number of uncharacterized putative effector proteins. In this study, we identified a putative secreted protein, CsSp1, with a classic N-terminal signal peptide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 84 publications
2
15
0
1
Order By: Relevance
“…This result indicated that BxSCD3 is a translocated effector. A similar result was found in Bipolaris sorokiniana effector CsSp1, which triggered plant immunity in both the nucleus and the cytoplasm of N. benthamiana cells [ 32 ]. There was no NLS or other organelle localization signals in CsSp1, so the localization of CsSp1 was predicted to be influenced by the target protein, and CsSp1 target proteins are present in both the nucleus and the cytoplasm of plants [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This result indicated that BxSCD3 is a translocated effector. A similar result was found in Bipolaris sorokiniana effector CsSp1, which triggered plant immunity in both the nucleus and the cytoplasm of N. benthamiana cells [ 32 ]. There was no NLS or other organelle localization signals in CsSp1, so the localization of CsSp1 was predicted to be influenced by the target protein, and CsSp1 target proteins are present in both the nucleus and the cytoplasm of plants [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…A similar result was found in Bipolaris sorokiniana effector CsSp1, which triggered plant immunity in both the nucleus and the cytoplasm of N. benthamiana cells [ 32 ]. There was no NLS or other organelle localization signals in CsSp1, so the localization of CsSp1 was predicted to be influenced by the target protein, and CsSp1 target proteins are present in both the nucleus and the cytoplasm of plants [ 32 ]. Thus, the localization of BxSCD3 may also be influenced by the target protein, which may be also present in both the nucleus and the cytoplasm of plants.…”
Section: Discussionsupporting
confidence: 77%
“…B. sorokiniana Lankao 9-3 was provided by Dr. Shengli Ding’s laboratory from Henan Agricultural University, as previously described [ 38 ] and was preserved on potato dextrose agar (PDA) medium at 4 °C. The old strain was transferred to a fresh new medium every two months to avoid compromising the strain’s vitality.…”
Section: Methodsmentioning
confidence: 99%
“…B. sorokiniana spores were obtained as previously described [ 38 ]. The mycelia of B. sorokiniana were incubated on a PDA medium for 5 d at 28 °C under alternating light and dark conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation